(Hexafluorosilicato‐κ2F, F′)bis(1, 10‐phenanthroline‐κ2N, N′)zinc(II) methanol monosolvate. (5th September 2013) - Seidel, Rüdiger W.; Dietz, Christina; Breidung, Jürgen; Goddard, Richard; Oppel, Iris M.
Abstract : The title compound, [Zn(SiF6 )(C12 H8 N2 )2 ]·CH3 OH, contains a neutral heteroleptic tris‐chelate Zn II complex, viz. [Zn(SiF6 )(phen)2 ] (phen is 1, 10‐phenanthroline), exhibiting approximate molecular C 2 point‐group symmetry. The Zn II cation adopts a severely distorted octahedral coordination. As far as can be ascertained, the title complex represents the first structurally characterized example of a Zn II complex bearing a bidentate‐bound hexafluorosilicate ligand. A density functional theory study of the isolated [Zn(SiF6 )(phen)2 ] complex was undertaken to reveal the influence of crystal packing on the molecular structure of the complex. In the crystal structure, the methanol solvent molecule forms a hydrogen bond to one F atom of the hexafluorosilicate ligand. The hydrogen‐bonded assemblies so formed are tightly packed in the crystal, as indicated by a high packing coefficient (74.1%).